2021
DOI: 10.1002/pds.5347
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury identification for pharmacoepidemiologic studies: Use of laboratory electronic acute kidney injury alerts versus electronic health records in Hospital Episode Statistics

Abstract: Purpose A laboratory‐based acute kidney injury (AKI) electronic‐alert (e‐alert) system, with e‐alerts sent to the UK Renal Registry (UKRR) and collated in a master patient index (MPI), has recently been implemented in England. The aim of this study was to determine the degree of correspondence between the UKRR‐MPI and AKI International Classification Disease‐10 (ICD‐10) N17 coding in Hospital Episode Statistics (HES) and whether hospital N17 coding correlated with 30‐day mortality and emergency re‐admission af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…The latter is close to our finding of AKI diagnosis in almost 90 per 100,000 population, indicating that the hospital staff considered mainly advanced stages for coding by ICD, even if dialysis was required in less than 8% of hospitalizations. The underreporting of total AKI incidence by ICD coding in administrative databases compared with laboratory-based detection has also been observed in other studies [13,14]. However, even though our analysis identified mainly patients with advanced stages, it provides important insights into the disease burden.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…The latter is close to our finding of AKI diagnosis in almost 90 per 100,000 population, indicating that the hospital staff considered mainly advanced stages for coding by ICD, even if dialysis was required in less than 8% of hospitalizations. The underreporting of total AKI incidence by ICD coding in administrative databases compared with laboratory-based detection has also been observed in other studies [13,14]. However, even though our analysis identified mainly patients with advanced stages, it provides important insights into the disease burden.…”
Section: Discussionsupporting
confidence: 56%
“…On the other hand, the observed between-province differences might also reflect ICD coding practice, that differed severalfold between hospitals [5]. The sensitivity of AKI detection in administrative databases was close to 30% in historical studies [25][26][27] but is reported to be higher in modern analyses where an average of 50% of stage 1, 70% of stage 2, and 80% of stage 3 AKI episodes were assigned ICD codes by the hospital personnel (with severalfold differences in coding frequency between hospitals) [5,13]. The rules for coding and reimbursement were the same for medical facilities in all the Lombardy provinces, and the exact reasons for the between-province differences need to be studied further.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AKI staging and severity could not be determined as serum creatinine measures are not available from HES-APC. We used ICD-10 codes recorded as part of a hospital admission to define AKI, which have been validated and are considered to have high specificity in identifying AKI [ 27 ] but some AKI cases may still have been missed, especially less severe presentations. The journey of a colorectal cancer patient through the healthcare system is likely different to that of an individual with no history of cancer, as evidenced by the difference in follow-up time, a limitation which we acknowledge.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature reports varying algorithms to define AKI in health care databases (Table 4). 78 Below, we summarize common features of these definitions that require attention as they can affect the generalizability or validity of study findings. We illustrate this using our third example question: "After AKI, what is the causal effect of stopping versus continuing renin-angiotensin system inhibitors on the risk of recurrent AKI?"…”
Section: Considerations For Choosing Aki Definitionsmentioning
confidence: 99%